2010
DOI: 10.7326/0003-4819-153-12-201012210-00007
|View full text |Cite
|
Sign up to set email alerts
|

Reconsidering the Approach to Prevention Recommendations for Older Adults

Abstract: The U.S. Preventive Services Task Force (USPSTF) bases its recommendations on an evidence-based model of clinical prevention that focuses on specific diseases, well-defined preventive interventions, and evidence of improved health outcomes. Applying this model to prevention for very old patients has been problematic for several reasons: Many geriatric disorders have multiple risk factors, interventions, and expected outcomes; older adults are not often represented in clinical trials; and important outcomes may… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
33
0
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 13 publications
0
33
0
1
Order By: Relevance
“…The challenge for older persons with multiple conditions is that these trade-offs encompass both many different specific diseases and non disease-specific health domains. 2 One approach to this challenge is to consider treatment in terms of its effects on a set of universal, cross-disease outcomes and to use older persons’ prioritization of these outcomes as an assessment of preferences. These outcomes, examples of which include length of life, physical and cognitive function, and symptoms, include basic domains recognized to be the key components of health.…”
Section: Introductionmentioning
confidence: 99%
“…The challenge for older persons with multiple conditions is that these trade-offs encompass both many different specific diseases and non disease-specific health domains. 2 One approach to this challenge is to consider treatment in terms of its effects on a set of universal, cross-disease outcomes and to use older persons’ prioritization of these outcomes as an assessment of preferences. These outcomes, examples of which include length of life, physical and cognitive function, and symptoms, include basic domains recognized to be the key components of health.…”
Section: Introductionmentioning
confidence: 99%
“…As has been seen with the development of the fields of adolescent and geriatric medicine, established guidelines may also accelerate the expansion of that evidence base by catalyzing research to modify existing interventions, develop new interventions, and facilitate tailored methods to improve surveillance, outreach, access, and outcome measurements. [10][11][12][13] As Ozer and colleagues have demonstrated, there are evidence-based guidelines that can inform preventive health care for young adults. However, in their current forms, research suggests that these guidelines are not being widely used and that gains in preventive health care for young adults are not being efficiently made.…”
mentioning
confidence: 99%
“…The U.S. Preventive Services Task Force has stated that it is important to develop preventive measures specifically for the geriatric population because its anticipated, unprecedented growth in the near future will result in increased attention to preventive services. In addition, the Task Force has indicated that it will need to adjust its methodology because the benefits, harms, and preventive health care concerns of younger adults may not be entirely transferable to the older population (Leipzig et al, 2010).…”
Section: Bulletin Of the Menninger Clinicmentioning
confidence: 99%